HUBUNGAN EFIKASI DIRI DAN DUKUNGAN SOSIAL DENGAN BULLYING PADA REMAJA DI SMPN 2 SEPATANKABUPATEN TANGERANG - Dwi Arini, (2021)
Teenagers face the problem of bullying which requires social support from those around them in order to have confidence in their abilities. This study aims to determine the relationship between self-efficacy and social support with bullying in adolescents at SMPN 2 Sepatan, Tangerang Regency. The research design is cross sectional using Spearman correlation test to analyze the relationship between variables. The sampling technique was simple random sampling with 127 respondents. The instrument uses a self-efficacy questionnaire, Multidimensional Scale of Perceived Social Support, and the revised Olweus Bully or Victim Questionnaire. There is a significant relationship between self-efficacy and bullying (p-value 0.031) and there is a significant relationship between social support and bullying (p-value 0.001). The research implication is knowing the relationship between self-efficacy and social support for victims of bullying in adolescents. This study is also useful for parents that teenagers need support in going through the effects of bullying.